2020
DOI: 10.1371/journal.pone.0240931
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drought on the abundance and distribution of non-breeding shorebirds in central California, USA

Abstract: Conservation of migratory species requires anticipating the potential impacts of extreme climatic events, such as extreme drought. During drought, reduced habitat availability for shorebirds creates the potential for changes in their abundance and distribution, in part because many species are highly mobile and rely on networks of interior and coastal habitats. Understanding how shorebirds responded to a recent drought cycle that peaked from 2013 to 2015 in central California, USA, will help optimize managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Surrounding these core habitat needs, our study identified a large time frame over which additional habitat may be needed, particularly in drier years, ranging from early January through early May. Our finding of reduced habitat availability for migratory shorebirds in the Central Valley in recent years is noteworthy because it is consistent with what was predicted to result from ongoing climatic warming (Barbaree et al, 2020; Matchett & Fleskes, 2017). From 1895 to 2017, the highest annual mean air temperatures ever recorded in California occurred in the last four years (coincident with our study), with 2014 being the warmest on record, followed by 2015, 2017, and 2016 (WRCC, 2018).…”
Section: Discussionsupporting
confidence: 77%
“…Surrounding these core habitat needs, our study identified a large time frame over which additional habitat may be needed, particularly in drier years, ranging from early January through early May. Our finding of reduced habitat availability for migratory shorebirds in the Central Valley in recent years is noteworthy because it is consistent with what was predicted to result from ongoing climatic warming (Barbaree et al, 2020; Matchett & Fleskes, 2017). From 1895 to 2017, the highest annual mean air temperatures ever recorded in California occurred in the last four years (coincident with our study), with 2014 being the warmest on record, followed by 2015, 2017, and 2016 (WRCC, 2018).…”
Section: Discussionsupporting
confidence: 77%
“…Consistent with our results that show the best performing models used a combination of both real‐time and long‐term data, some taxa, such as whales, may respond to both historical and contemporaneous environmental conditions (Abrahms et al, 2019 ). Previous studies have demonstrated that shorebirds typically shift their distributions as a function of dynamic within‐year water availability, both in the Central Valley (Barbaree et al, 2018 , 2020 ) and elsewhere (Maclean et al, 2008 ; Steen et al, 2018 ). The tendency to visit the same site every year may simply be a function of available habitat.…”
Section: Discussionmentioning
confidence: 99%
“…We combined multiple data sets on the occurrence of five species of shorebirds (treating long‐ and short‐billed dowitchers as a single taxa), including structured data sets and complete checklists in the opportunistically collected eBird reference data set (ERD) through 2016 (Sullivan et al, 2009 ). The structured data sets (Barbaree et al, 2020 ; Golet et al, 2018 ; Reiter et al, 2011 ; Sesser et al, 2016 , 2018 ; Shuford et al, 2019 ; Strum et al, 2013 ) were largely conducted during times of year and in rice and other agricultural habitats where, given flooding, shorebirds were expected. To supplement the spatial and temporal extent of the structured data, we included eBird observations that used sampling protocols that closely matched the structured data: namely, observations collected during daylight hours and by stationary observers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This Research Topic highlights that rainfall impacts birds in diverse ways, and Rosamond et al show that Dickcissel (Spiza americana) populations decline with increasing amounts of summer rainfall. However, drought also influences the distribution of breeding birds (Barbaree et al, 2020;Campos-Cerqueira and Aide, 2021) and particularly so in arid regions (Herremans, 2004). Bourne et al advance our understanding of adaptive responses to drought by showing that Southern Pied Babblers (Turdoides bicolor) in the Kalahari Desert in South Africa significantly reduce their reproductive effort during breeding seasons characterised by drought but subsequently increase their reproductive effort during the breeding seasons immediately following droughts.…”
Section: Impact Of Weather On Birds During Nest Building and Incubationmentioning
confidence: 99%